Use of Standardized Patient Encounters as Predictors of Fieldwork Performance: A Pilot Study - Linda Frasier; John V. (Johnny); Ashley Fecht (Scholarworks @ WMU, 2022)
Background: Although standardized patient encounters (SPEs) are being used in occupational therapy (OT) education, limited literature exists on the value these experiences have on OT student learning outcomes and preparation for fieldwork. This study sought to examine if SPEs had the potential to predict Level II A fieldwork performance. Method: This study used a retrospective analysis of 35 entry-level OT students. Independent variables included demographics (enrollment in an entry-level OT master's or doctoral degree, age, and overall grade point average) and SPE performance. The fieldwork Level II A final performance evaluation score was used as the dependent variable. Hierarchical regression analysis was used with demographic variables as the first model to compare the addition of SPEs in predicting Level II A fieldwork performance scores. Results: The full model of demographics and SPE was statistically significant and accounted for 29% of the variance in the fieldwork Level II A performance scores (p = .031). SPEs accounted for an additional statistically significant amount of variance (17%), above and beyond demographic variables (p = .012). Discussion: These results indicate the potential value of SPEs in identifying students requiring additional preparation before embarking on clinical practice in their Level II A fieldwork.